(untitled) (Journal of Science and Technology, 2016)
This paper identifies the type and sources of the materials for the preparation of ceramic glazes in Ghana. It deals with the formation of glazes; the major chemicals and their materials sources of supply and finally lists the common raw materials obtainable in different parts of the country. The minerals are listed under major rock types and their chemical constituents in percentages are quoted. The chemicals that occur in insignificant quantities have been lumped under the heading ‘others’. This has been done for easy identification and comparison. It is believed an adequate information on raw materials for glaze preparation would go a long way to stimulate interest in research institutions and in the universities in the country in that direction.